Propane oxidation on Pt-WO3/gamma -AL2O3 catalytic systems - Silva,M.A.Pereira da (2003)
The oxidation of propane on was studied with Pt-xWO3/Al2O3 catalysts was studied ,by varying the concentration of tungsten sublayer. Thermal analysis and XRD in situ showed that the enrichment of tungsten at the surface is associated with the formation of HxWO3 bronze. FTIR results with C3H8 and O2 indicated that the catalyst surface properties and the interaction between W and Pt were modified. These modified surface complexes prevented the formation of acetates and formate species. The addition of W increased the activity of Pt/Al2O3 towards in C3H8 oxidation. Tungsten was the main responsible for the stability of the bimetallic catalysts in the presence of water.